Formes brèves et microrécits - Alain Montandon (Les Cahiers de Framespa)
After some remarks on the short and the brief, and then on textual space and time in the short form from the reader’s point of view, the author considers reader enthusiasm for micro-narratives. With a survey from Antiquity through canonical European literature to the present day, the author singles out the features of the brief form in its different varieties, and studies their modes of insertion within larger ensembles such as the miscellany and the novel.